Evaluation in the teaching practicum of the english program at the universidad de la amazonía (2009)
The following article summarizes the research study which sought to examine the process of evaluation in the teaching practicum of the undergraduate program in English language teaching at Universidad de la Amazonía, in Florencia, Caquetá, Colombia. The purpose of this project was to establish which evaluation paradigm promotes the professional development of the student teacher whilst inside the actual conditions of her/his work. The research process was based on participant, non- participant observations and interviews with a group of 17 student teachers and their counsellor. The results showed some features of the critical paradigm of evaluation that contributed to the professional development of the subjects involved in the practicum (student teachers and counsellor). It was also found that it is very important to encourage the formation of critical and progressive professionals. Key words: Critical evaluation, professional teacher development, teaching practicum, action research El siguiente artículo resume la investigación que buscó examinar el proceso de evaluación en las prácticas de formación profesional docente en el programa de Licenciatura en Inglés de la Universidad de la Amazonía, en Florencia (Caquetá - Colombia). El propósito de este proyecto fue establecer qué paradigma de evaluación promueve el desarrollo profesional del maestro en formación en medio de las condiciones en las cuales desarrolla su labor. El proceso de investigación se basó en las observaciones participantes y no participantes, y en una entrevista a profundidad con un grupo de 17 maestros en formación y su consejero. Los resultados mostraron algunas características del paradigma crítico de evaluación que contribuyeron al desarrollo profesional de los sujetos involucrados en la práctica (maestros en formación y consejero). También se encontró que es muy importante promover la formación de profesionales críticos y progresivos. Palabras clave: Evaluación crítica, desarrollo profesional docente, prácticas de formación docente, investigación acción